Injectable bioresorbable conductive hydrogels for multimodal brain tumor electroimmunotherapy - Yadav, Amit Singh; Aydemir, Umut ; 0000-0002-0128-7889; Hellman, Karin; Ekström, Peter; Mousa, Abdelrazek H; Li, Jiaxin; Shameem, Muhammad Anwar; Dicko, Cedric ; 0000-0001-6377-3500; Bengzon, Johan; Ek, Fredrik ; 0000-0002-5651-8445; Hjort, Martin ; 0000-0002-3581-4720; Olsson, Roger ; 0000-0002-7107-3472 (Nature Communications, 2025)
Current electrode technologies are too rigid for safe and effective delivery of electrotherapy in the brain, and patients with glioblastoma continue to face a devastating prognosis, with median survival stalled at 15 months despite intensive treatment with surgery, radiation, and chemotherapy. But these conventional approaches potentially compromise immune function, underscoring the urgent need for therapies that activate, rather than suppress, the immune system. Therefore, we introduce injectable conductive hydrogels engineered to match the softness of brain tissue while exhibiting electrical conductivities up to three orders of magnitude higher than any previously reported injectable hydrogels. They can be implanted through minimally invasive syringe capillaries as narrow as 30 µm-avoiding brain tissue damage-and via convection-enhanced delivery (CED) or endovascular catheters, the latter potentially eliminating the need for open brain surgery. Additionally, it can drape a resection cavity to eliminate residual tumor cells. In human glioblastoma tumors in the chicken chorioallantoic membrane model, implantation of the electrode using CED, followed by irreversible electroporation, obliterated tumors within three days. Other injection techniques impaired tumor growth, induced immunogenic cell death, and a robust infiltration of helper and cytotoxic T cells, alongside macrophages, highlighting the immune-activating and tumor-targeting capabilities.
© 2025. The Author(s).
Keywords: Hydrogels/chemistry; Animals; Brain Neoplasms/therapy; Humans; Glioblastoma/therapy; Immunotherapy/methods; Cell Line, Tumor; Electric Conductivity; Injections; Electrochemotherapy/methods; Chick Embryo; Chickens; Mice; Combined Modality Therapy; Electroporation; Cancer therapy; Materials science